Partycypacja polityczna w Polsce - Tybuchowska-Hartińska, Karolina (Political Preferences, 2015)
Political participation in Poland Basing on research carried out on a representative group of Poles, as part of a national research project called „Political preferences. Attitudes- IdentitiesBehaviours", it can be concluded that respondents the most often point expressing their beliefs through petitions (23%), local initiatives (21%) and demonstrations (12%). Research shows that men more frequently than women express their opinions through petitions (54,2%-45,8%), local initiatives (54,3%-45,7%) and demonstrations (61,6%-38,4%). Inhabitants of villages and towns over 200 thousand people were nearly two times more active than citizens of medium-sized villages. Having at least a secondary school education definitely increases people's activity (approx. 40%), more than having a vocational education (approx. 13%). Expressing views is also dependent on age because younger people do it more frequently than elder ones. The most indicated were individuals in the age group 25-34 (62%), more rarely although in comparable proportions people aged 18-24 and 35-44 while in the next age groups that activity drops significantly. People aged 18-24 and 45-54 the most willingly take part in demonstrations. People aged 25-34 sign petitions and engage in local initiatives. Among citizens in the age of 55 and more there is not evident diversity in the forms of participation. The differences in the behaviour of people with various views are also highlighted. Those who declare themselves as left wing prefer petitions (39%) against local initiatives (35%) and demonstrations (26%). Centrist voters the most often choose petitions (49%) against local initiatives (34%) and demonstrations (17%). And people who declare themselves as right wing mainly indicate local initiatives (43%) against petitions (36%) and demonstrations (21%). But those citizens, who could not determine them- selves, the most often decide to petitions (49%) against local initiatives (32%) and demonstrations (19%). Taking under consideration declared political views there are no significant differences when it comes to membership in political parties, trade unions, non-government organizations and local associations. Greater disproportions are highlighted when comparing belonging to different types of organizations. Regardless of the opinions the most popular are local associations, followed by non-government organizations, trade unions, and the least political parties. In conclusion, it can be said that the political participation in Poland clearly indicates who is more frequent and who is more seldom willing to be active in this area. It seems to be an important clue for those wishing to take effective activities to increase the involvement of citizens. Key words: political participation, Poland, local initiatives,demonstrations, petitions